A Study of Chinese University EFL Learners’ Foreign Language Listening Anxiety, Listening Strategy Use and Listening Performance - Meihua Liu; Juliet Thondhlana (Indonesian JELT, 2015)
The present study examined foreign language (FL) listeninganxiety and listening strategy use in relation to FL listeningcomprehension performance of 1702 undergraduate EFLlearners from 5 universities in China. Analyses of the surveydata revealed the following findings: (1) more than half of thestudents generally did not feel anxious when listening toEnglish, were low in English listening proficiency, were notconfident in or satisfied with their English listening proficiency,and usually moderately used different types of strategies whenlistening to English; (2) compared with their femalecounterparts, the male students felt significantly more anxiouswhen facing listening activities and less satisfied with theirEnglish listening proficiency, used significantly more often thememory/attention/understanding-related strategies and were lessproficient in English, employed significantly more often ‘lessactive listener strategies’ (FLLSUS6), but significantly lessfrequently the strategies of negotiation for meaning (FLLSUS1),maintaining fluency (FLLSUS2), getting the gist (FLLSUS4),and nonverbal strategies (FLLSUS5), (3) all FLLAS (ForeignLanguage Listening Anxiety Scale) and FLLSUS (ForeignLanguage Listening Strategy Use Scale) scales were highlysignificantly correlated with each other and the students’listening comprehension performance, and (4) FLLSUS6,FLLAS2, FLLAS3, FLLAS1, FLLSUS2, and FLLSUS1 weregood predictors of English listening comprehensionperformance.Keywords: foreign language, listening anxiety, listeningstrategy use, listening comprehensionperformance